Die missionêre waarde van Belhar en die NG Kerk-familie se herenigingsgesprek - De Beer, JM; Van Niekerk, AS (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
The missional value of Belhar and the DRC-family’s reunification talks The two questions are raised: a) Does Belhar in fact polarize members of the DRC-family? and b) Is Belhar in fact a stumbling block in the way of church unity? They are discussed to illuminate the contradictions embodied in these questions. It is then shown that the usage of the missional value of Belhar can point towards a direction out of the perceived dilemma in the current reunification talks in the family of DRC churches. The missional value of Belhar is explained with reference to the liberation-effect that Belhar has had on the DRC’s missional relevance during the eighties and thereafter. A missional valuation of Belhar as a possible alternative to the URCSA’s insistance on official acceptance of the confession by the DRC, forms the conclusion of the article.